The impact of technological and business innovation on economic performance: Mediating role of government support - Alateeg, Sultan; Alayed, Sura (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of technological innovation, business innovation, and government support on economic performance within Saudi Arabia's manufacturing sector. It aims to explore both direct and indirect relationships, emphasizing the mediating role of government support. A cross-sectional research design was employed, with data collected from managerial-level employees using a structured questionnaire. Structural equation modeling (SEM) was utilized to analyze the relationships between key variables. The results indicate that technological innovation (β = 0.488) and business innovation (β = 0.467) significantly influence government support, which in turn has a strong positive effect on economic performance (β = 0.88). Furthermore, government support mediates the relationship, with technological innovation (β = 0.43) and business innovation (β = 0.411) indirectly enhancing economic performance. The findings highlight the crucial role of innovation and government policies in fostering economic growth. Strengthening collaboration between businesses and government entities can create an innovation-driven ecosystem that supports sustainable development. This study provides insights for policymakers and business leaders on leveraging innovation and government support to enhance economic performance. Aligning strategies with Saudi Arabia’s Vision 2030 can help establish a competitive and sustainable manufacturing sector.